Intercontinental transport of nitrogen oxide pollution plumes - Wenig, M.; Spichtinger, N.; Stohl, A.; Held, G.; Beirle, S.; Wagner, T.; Jahne, B.; Platt, U. (European Geophysical Soc, 2003)
We describe the first satellite observation of intercontinental transport of nitrogen oxides emitted by power plants, verified by simulations with a particle tracer model. The analysis of such episodes shows that anthropogenic NOx plumes may influence the atmospheric chemistry thousands of kilometers away from its origin, as well as the ocean they traverse due to nitrogen fertilization. This kind of monitoring became possible by applying an improved algorithm to extract the tropospheric fraction of NO2 from the spectral data coming from the GOME instrument.As an example we show the observation of NO2 in the time period 4-14 May, 1998, from the South African Plateau to Australia which was possible due to favourable weather conditions during that time period which availed the satellite measurement. This episode was also simulated with the Lagrangian particle dispersion model FLEXPART which uses NOx emissions taken from an inventory for industrial emissions in South Africa and is driven with analyses from the European Centre for Medium-RangeWeather Forecasts. Additionally lightning emissions were taken into account by utilizing Lightning Imaging Sensor data. Lightning was found to contribute probably not more than 25% of the resulting concentrations. Both, the measured and simulated emission plume show matching patterns while traversing the Indian Ocean to Australia and show great resemblance to the aerosol and CO2 transport observed by Piketh et al. (2000).